Recientes contribuciones latinoamericanas a la Filosofía de la Ciencia - Álvarez Bautista, Juan Ramón (1988)
This text is based upon the lecture given by the author at the "Jornadas sobre la filosofía en América Latina" held in October 1988 at the University of Puerto Rico (Mayagüez) steered by the Philosophical Society of Puerto Rico. The main point stressed here is that the existence and identity of Latin American philosophy are neither geographical nor biological, but historical. Contributions made by Latin American philosophers (Bunge' Moulines, Torretti) to the view of science as approximat(iv)e knowledge open the door wide for the author's attempt to discern the meaning and reference of the expression "Latin American philosophy" within the range marked out by two endpoints: outstanding philosophical works, on the one hand, and weak institutionalization of "reason" in history, on the other, understood in terms of the Kantian notions of academic and worldly philosophy, respectively. Thus posed, the problem of philosophy in Latin America drives us right into Latin America's own history.
Keywords: Ciencia -- Filosofía; América Latina -- Historia